The impact of informal control on the innovation performance of female technology professionals from the perspective of role pressure - Zeng, Xiangfei; Cao, Mengyan; Hu, Jingjing; Zhang, Wenpei (Frontiers in Psychology, 2024)
This study distributed questionnaires to female technology professionals in China's STEM field to investigate the effect of informal control on their innovation performance from a psychological perspective. It further explored the mediating role of role pressure and the moderating role of environmental turbulence in this relationship. This study primarily utilized AMOS 24.0 to develop structural equation models, and employed PROCESS 24.0 and SPSS 26.0 for data analysis purposes. The findings reveal that informal control positively predicted the innovation performance of female technology professionals in STEM field. Role pressure partially mediates this relationship, while environmental turbulence positively moderates the relationship between informal control and innovation performance among female technology professionals in STEM field. Theoretically, this research enriches the individual-level approaches to enhancing management control effectiveness. Practically, it aids managers in focusing on the psychological well-being of female technology professionals in STEM field, thereby facilitating the judicious selection of management control methods. The study's conclusions aim to provide logical guidance for enterprises to further strengthen their attention and support for female technology professionals in STEM field. Simultaneously, it offers a theoretical foundation for enhancing their innovative capabilities.